NEW PSYCHOSOCIAL RISKS HUMAN RESOURCES EXECUTIVES FACE WITH: PSCHOLOGICAL AGREEMENTS, AGEING WORKFORCE, INSTABILITY BETWEEN WORK – PRIVATE LIFE AND MOBBING - Gokhan Ofluoglu (European Scientific Journal, ESJ, 2013)
Important changes that has recently taken place in working-occupational-professional life has led to new risk factors to emerge in the realm of occupational safety and health. These factors which remain outside physical, biological and chemical risks and has adverse effects on occupational health and safety are termed psychosocial risk factors. Psychosocial risks are identified as social and organizational adversary activities which emerge due to the methods applied and arranged in relation to work life that give rise to psychological and physical harms. The main aim of this study is to identify the new psychosocial risks that may influence the working lives of the individuals that take part in the social, economic, cultural and particularly technological changes and state which precautions the human resources units have to take under such menace. The subjects of psychological agreements, ageing workforce, work – private life conflicts, psychological harrassment at work place and mobbing are the four prominent psychosocial risk components that are dealt with in this context. Hence the precautions that the human resources executive has to take is discussed to reduce the components of the risks to a minimum.